Physical and mechanical properties of semi-automatic MIG welding of AA5083H116 materials - Mudjijana Mudjijana (JMPM (Jurnal Material dan Proses Manufaktur), 2018)
Metal inert gas (MIG) welding speed can be carried out manually for complicated components and can also be controlled using computer numerical control (CNC). The purpose of the research is to investigate the effect of CNC welding speed on physical and mechanical properties of AA5083H116. AA5083H116 base metal, ER5356 electrodes, welding speeds of 8, 10, 12 mm/s, current of 120 A, voltage of 19 V, filling speed of 27 mm/s, argon gas rate of 15 liter/minute were used. Distortions after welding were measured using dial indicators, thermal cycles was recorded using type-K thermocouple using National instruments NI USB-9162 apparatus connected to a CPU. The physical properties was analyzed using SEM and EDS for only the best mechanical properties, and the mechanical properties were evaluated using Vickers microhardness, and tensile and bending universal testing machine. The results show that at the welding speed of 8 mm/s automatic regulated was the best mechanical properties compare to previous study at the welding speed of 10 mm/s manually regulated. However, SEM images show that there were several micro cracks at its grain, and several magnesium precipitates can be noticed from the EDS analysis.